A Conspiracy of Paper? William Paterson and the Mysterious Origins of Banking and Company Law - John Farrar (Bond Law Review)
This article examines the creation of the Bank of England and other contemporary banks, the Scottish Darien Scheme and the South Sea Bubble. It considers the role of William Paterson, a progressive Scottish merchant and economist, in all of these and the negotiations over the Act of Union of England and Scotland. The article reflects on the use of legislation and royal charters, together with the idea of joint stock and negotiability. It seeks to untangle the complex relationships of the Darien Company and the South Sea Company to banking operations of the time. Although Paterson had a minor role in the South Sea company, it was based on some of his ideas but he opposed the ultimate scheme to take over the national debt in exchange for stock which followed the policies of his compatriot John Law for France. Law in his turn had been influenced by the Bank of England and the Darien Scheme fund raising. The Bubble Act 1720, responding to the panic caused by collapse of bubble companies, was passed a year after his death and impeded the development of company and banking law for over a century.